Ribosome heterogeneity in development and disease - Gao, Yuen; Wang, Hongbing (Frontiers in Cell and Developmental Biology, 2024)
Traditionally viewed as a fixed and homogeneous machinery for protein synthesis, the ribosome is increasingly recognized for its heterogeneity, as indicated by emerging studies highlighting the functional relevance of specialized ribosomes. However, whether ribosome heterogeneity is merely an outcome limited to specific conditions or a pervasive cellular phenomenon remains unclear, and existing evidence on the extensive existence of ribosome heterogeneity is scant. Here, we leveraged existing proteomic data and employed ribosome ratio-omics (RibosomeR), which comprehensively analyzes ribosome protein stoichiometry across various biological samples exhibiting distinct functions, developmental stages, and pathological states. Using the 80S monosome proteomic data, RibosomeR analysis unveils significant ribosome heterogeneity across different tissues, including fat, spleen, liver, kidney, heart, and skeletal muscles. Furthermore, examination of testes at various stages of spermatogenesis reveals distinct RibosomeR signatures during tissue development. Analysis of the whole cell proteomic data finds that RibosomeR undergoes dynamic changes during in vitro neuronal maturation, indicating functional associations with specific molecular aspects of neurodevelopment. In pathological contexts, RibosomeR signatures in gastric tumors demonstrate functional links to pathways associated with tumorigenesis. Additionally, dynamic alterations in RibosomeR are observed in macrophages following immune challenges. Collectively, our investigation across a diverse array of biological samples underscores the presence of ribosome heterogeneity, while previous studies observed functional aspects of ribosome specialization, in cellular function, development, and disease. The RibosomeR barcode serves as a valuable tool for elucidating these complexities.